Literasi Budaya Pada Anak di Rumah Pintar YAFSI “Pengolahan Sampah Plastik Menjadi Pot Bunga” - Enjelina Panjaitan, Juwita; Siregar, Hairani; Utama Ritonga, Fajar (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
The rapid development of the times has made many changes in the entire scope of human life. From social behavior, technology, environment, climate and many other things. The environment is one of the things that is close to human life. The behavior towards waste has become a culture that is rooted in society. This has an impact on the mindset of the community regarding waste that is not appropriate. It takes care and concern for cleanliness in the environment. This form of concern can start from the family where there are children in it. According to R.A. Kosnan